2019
DOI: 10.3390/antiox8080285
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Implications of Reactive Oxygen Species Production by Mitochondrial Complex I Reverse Electron Transport

Abstract: Mitochondrial reactive oxygen species (ROS) can be either detrimental or beneficial depending on the amount, duration, and location of their production. Mitochondrial complex I is a component of the electron transport chain and transfers electrons from NADH to ubiquinone. Complex I is also a source of ROS production. Under certain thermodynamic conditions, electron transfer can reverse direction and reduce oxygen at complex I to generate ROS. Conditions that favor this reverse electron transport (RET) include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 100 publications
(194 reference statements)
2
50
0
Order By: Relevance
“…In the mitochondrial transport chain, flavoprotein reductase forms ROS by direct reduction of O 2 and via the mediation of quinones. [ 104 ]. Superoxide (O 2 −• ) is produced by XO in the reperfusion phase of ischemia, LOX, COX, and NADPH-dependent oxidase [ 105 ].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…In the mitochondrial transport chain, flavoprotein reductase forms ROS by direct reduction of O 2 and via the mediation of quinones. [ 104 ]. Superoxide (O 2 −• ) is produced by XO in the reperfusion phase of ischemia, LOX, COX, and NADPH-dependent oxidase [ 105 ].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Reverse electron transfer (RET) catalyzed superoxide production was discovered by Chance and co-workers in 1967 [ 71 ], and was considered irrelevant, until Murphy’s group showed that RET contributed to cardiac ischemia reperfusion injury (IRI) in 2013–2014 [ 72 , 73 ]. We now know that RET plays several important physiological (e.g., sleep, lifespan and O 2 sensing) and pathological (e.g., in organ transplantation) roles [ 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. Robb and colleagues [ 81 ] have identified the factors that govern RET: a highly reduced Q pool and near maximal Δ p .…”
Section: Mechanisms Of Mitochondrial Ros Production: the Knownmentioning
confidence: 99%
“…In addition, oxidized lipids and mitochondrial redox state were assayed, and mito-dR decreased signs of oxidative stress. In many contexts, however, decreased rather than increased PMF is associated with alleviated oxidative stress [6, 79,80], especially in Parkinson's disease models [81][82][83][84].…”
Section: Mito-drmentioning
confidence: 99%